2014
DOI: 10.1186/1477-7525-12-94
|View full text |Cite
|
Sign up to set email alerts
|

What contributes to a good quality of life in early dementia? awareness and the QoL-AD: a cross-sectional study

Abstract: BackgroundSelf-report quality of life (QoL) measures for people with dementia are widely used as outcome measures in trials of dementia care interventions. Depressed mood, relationship quality and neuropsychiatric symptoms predict scores on these measures, whereas cognitive impairment and functional abilities typically do not. This study examines whether these self-reports are influenced by personality and by the person’s awareness of his/her impairments. A strong negative association between QoL and awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 42 publications
9
94
4
Order By: Relevance
“…Relationship quality, rated by the person with dementia, has been shown to be an important contributor to quality of life for people with dementia and is the cornerstone of relationship-centred care. 75 We also found that health-related quality of life for family carers significantly increased, indicating that carer involvement in cognitive-based interventions may increase carer well-being. This may be related to the fact that, although iCST was developed largely as a home-based, carer-led, individual cognitive stimulation approach, the intervention incorporated additional psychoeducational elements such as communication, opportunities to increase pleasant events for both carers and people with dementia, which are components less likely to be incorporated in group CST-based approaches.…”
Section: Secondary Outcomesmentioning
confidence: 64%
“…Relationship quality, rated by the person with dementia, has been shown to be an important contributor to quality of life for people with dementia and is the cornerstone of relationship-centred care. 75 We also found that health-related quality of life for family carers significantly increased, indicating that carer involvement in cognitive-based interventions may increase carer well-being. This may be related to the fact that, although iCST was developed largely as a home-based, carer-led, individual cognitive stimulation approach, the intervention incorporated additional psychoeducational elements such as communication, opportunities to increase pleasant events for both carers and people with dementia, which are components less likely to be incorporated in group CST-based approaches.…”
Section: Secondary Outcomesmentioning
confidence: 64%
“…The lack of self-reports for group comparison could allow differences in the dyad composition in the two populations to cause systematic proxy bias. Informants consistently rate QOL in people with dementia poorer than the self-reported QOL, and the reports on QOL of individuals with severe dementia, most reliant on their proxy voice, show the greatest discrepancy [29, 62, 65-67]. Proxy reports are also biased by informant-related factors, especially caregiver burden [68, 69], and dyad characteristics [70].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unravelling the relationship between needs and QOL is, of course, a more complex task than our relatively simply model can perform. Including predictors, such as depressed mood, quality of relationship and self-concept, in the model might account for a large percentage of the variance (Woods et al, 2014) This complexity will be investigated with the longitudinal data of this cohort. The strengths of this study are the size and variability of the cohort, as it represents people from eight European countries.…”
Section: Limitations and Strengthsmentioning
confidence: 99%